Studi Pemrosesan Akhir Sampah di Tempat Pengolahan Sampah Terpadu Bantargebang - Nur Ridha Amethysia; Gina Lova Sari (Jurnal Serambi Engineering, 2024)
According to Law No. 18 of 2008, waste management of landfill with open dumping system ito controlled landfill and sanitary landfill. TPST Bantargebang is a waste management company owned by the Government of DKI Jakarta, established in 1989, which initially used open dumping and has now switched to controlled landfill. The waste treatment is not optimal because the waste is only compacted and not covered with soil. The purpose of this research is to investigate the waste processing process in Bantargebang TPST landfill. This research method is descriptive qualitative, in July - September 2023. The amount of waste entering TPST Bantargebang in July 2023 averaged 7,226 tons/day with an average of 1,300 rites/day. Waste processing is carried out in 4 active zone landfills, including backfilling waste with the controlled landfill and rehabilitation for inactive zone landfills with landfill mining to extend the life of the landfill. Methane gas control has been carried out with technology that converts methane gas into electrical energy. The IPAS 3 test results show that the parameters exceed the quality standards. Waste processing at TPST Bantargebang uses the controlled landfill method, to optimise waste management, reduction technology, waste processing and landfill rehabilitation have been carried out